Mitochondrial dysfunction in vascular endothelial cells and its role in atherosclerosis - Qu, Kai; Yan, Fang; Qin, Xian; Zhang, Kun; He, Wen; Dong, Mingqing; Wu, Guicheng (Frontiers in Physiology, 2022)
The mitochondria are essential organelles that generate large amounts of ATP via the electron transport chain (ECT). Mitochondrial dysfunction causes reactive oxygen species accumulation, energy stress, and cell death. Endothelial mitochondrial dysfunction is an important factor causing abnormal function of the endothelium, which plays a central role during atherosclerosis development. Atherosclerosis-related risk factors, including high glucose levels, hypertension, ischemia, hypoxia, and diabetes, promote mitochondrial dysfunction in endothelial cells. This review summarizes the physiological and pathophysiological roles of endothelial mitochondria in endothelial function and atherosclerosis.